The Progress of the Plan A Short Survey of the Working of the Five Year Plan from April 1951 To September 1953 - Planning Commission (Planning Commission, 1954)
The objectives of the Five Year Plan have been set out in detail in the Report. Briefly, these objectives aim at initiating a process of development which will raise living standards and open out to the people new opportunities for a richer and more varied life. This implies: — the provision of increased employment and production by the most efficient utilization of the resources of the country; and the achievement of the largest measure of social justice possible.
Government of India Planning Commission